The handbook of global corporate treasury - Rajiv Rajendra (Wiley corporate F & A series., 2013)
A complete guide to operating a corporate treasury from a global perspective For CFOs and treasurers looking to re-align their treasuries with the growth of the global firm, bankers who seek to maximize the value they create for clients, treasury and finance firm employees, and even finance students, this book provides an easy-to-read approach to this exciting and increasingly complex world. It includes a toolkit that gives practitioners a reference point that they can adapt immediately for use in their firms, providing a low-cost, high-efficiency advisory solution they previously lac.